Hypertensive disorders of pregnancy and stroke: a univariate and multivariate Mendelian randomization study - Qu, Kang; Li, Mingxi; Yu, Peng; Jiang, Wei; Dong, Ming (Frontiers in Endocrinology, 2024)
Background Hypertensive disorders of pregnancy (HDP) are associated with an increased risk of stroke later in life in multiparous women. However, causality of these associations remains unclear. This study employed 2-sample univariate and multivariate Mendelian randomization (MR) to assess the causal connection between HDP and stroke. Methods Genetic variants for HDP and two subtypes were identified from recent large-scale genome-wide association studies and the FinnGen consortium. Stroke summary data were obtained from the MEGASTROKE consortium. The primary analytical approach for univariate MR was the inverse variance weighting method. Sensitivity analyses incorporated methods such as MR-Egger regression, weighted median, and maximum likelihood to ascertain the robustness of the results. Additionally, multivariable MR analyses were conducted to account for potential associative effects of hypertension and type 2 diabetes. Results Genetically predicted HDP was associated with a high risk of large artery atherosclerosis (odds ratio [OR]=1.50, 95% confidence interval [CI]: 1.17–1.91, P=1.13×10-3) and small vessel stroke (OR=1.29, 95% CI: 1.20–1.50, P=1.52×10-3). HDP may also correlate with ischemic stroke (OR=1.13, 95% CI: 1.04–1.23, P=4.99×10-3) and stroke (OR=1.11, 95% CI: 1.03–1.20, P=8.85×10-3). An elevated risk of small vessel stroke (OR=1.20, 95% CI: 1.01–1.43, P=3.74×10-2) and large artery atherosclerosis (OR=1.22, 95% CI: 1.01–1.47, P=4.07×10-2) may be related with genetically predicted susceptibility to gestational hypertension. Genetically predicted susceptibility to preeclampsia or eclampsia may be associated with an increased risk of stroke (OR = 1.10, 95% CI: 1.02–1.19, P = 1.16×10-2) and ischemic stroke (OR = 1.10, 95% CI: 1.02–1.20, P = 1.84×10-2). Type 2 diabetes mellitus and hypertension were identified as significant factors contributing to the association between HDP and stroke. Conclusions This study provides genetic evidence supporting an association between HDP and increased stroke risk bolstering HDP as a cerebrovascular risk factor.